RETRACTED: A Literature Review on Distribution System State Estimation. (2015) - Kumar, M.V. Likith; Prasanna, H.A Maruthi; Ananthapadmanabha, T.
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been retracted at the request of scientific committee of SMART GRID Technologies 2015. The authors have plagiarized part of a paper that had already appeared in Modelling Symposium (EMS), 2014 European, (2014) 303 - 308. DOI: 10.1109/EMS.2014.76 (http://ieeexplore.ieee.org/xpl/articleDetails.jsp?arnumber=7154016 ). One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.